Discriminating the trapped electron modes contribution in density fluctuation spectra. (17th August 2015) - Arnichand, H.; Sabot, R.; Hacquin, S.; Krämer-Flecken, A.; Bourdelle, C.; Citrin, J.; Garbet, X.; Giacalone, J.C.; Guirlet, R.; Hillesheim, J.C.; Meneses, L.
Abstract: Quasi-coherent (QC) modes have been reported for more than 10 years in reflectometry fluctuations spectra in the core region of fusion plasmas. They have characteristics in-between coherent and broadband fluctuations as they oscillate at a marked frequency but have a wide spectrum. This work presents further evidences of the link recently established between QC modes and the trapped electron modes (TEM) instabilities (Arnichand et al 2014 Nucl. Fusion 54 123017). In electron cyclotron resonance heated discharges of Tore Supra, an enhancement of QC modes amplitude is observed in a region where TEM cause impurity transport and turbulence. In JET Ohmic plasmas, QC modes disappear during density ramp-up and current ramp-down. This is reminiscent of Tore Supra and TEXTOR observations during transitions from the linear Ohmic confinement (LOC) to the saturated Ohmic confinement (SOC) regimes. Evidencing TEM activity then becomes experimentally possible via analysis of fluctuation spectra.